Influence Effective Tax Rate, Tunneling Incentive, Leverage, Bonus Mechanism and Exchange Rate on Transfer Pricing (Empirical Study of Mining Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period) - Septiani, Debi; Yuniarti Zs, Nensi; Ranidiah, Furqonti (Proceedings Series on Social Sciences & Humanities, 2025)
Study aims to determine the influence of effective tax rate, tunneling incentive, leverage, bonus mechanism and exchange rate on transfer pricing. The object of this research is mining companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The population of this study is the annual reports of 63 companies. The sample technique was selected based on certain criteria using purposive sampling techniques. There were 27 companies. The data collection method for this study used secondary data. The results of this study conclude that the Effective Tax Rate does not significantly influence Transfer Pricing. This is evidenced by the significance value of 0.460 > 0.05. Tunneling Incentives do not significantly influence Transfer Pricing. This is evidenced by the significance value of 0.537 > 0.05. Leverage does not have a significant effect on Transfer Pricing. This is evidenced by the significance value of 0.313 > 0.05. The bonus mechanism has a significant effect on Transfer Pricing. This is evidenced by the significance value of 0.000 < 0.05. Exchange Rate (ER) does not have a significant effect on Transfer Pricing (TP). This is evidenced by the significance value of 0.134 > 0.05.